The Improvement of Community Human Resources through Education at the Muhammadiyah Gempol Branch - Muhammad Ali Rohman; M. Sahrul Romadhon; Yudhistiral Yudhistiral; Trie Yoga; Anthonio Dion (Proceedings of The ICECRS, 2020)
Muhammadiyah is an organization which was founded on November 12, 1912, in which KH. Ahmad Dahlan and his students founded the organization in the Kauman area of ​​Yogyakarta. At that time, the Dutch were controlled by the Dutch so that KH. Ahmad Dahlan to establish the organization until now this history is remembered by Muhammadiyah people. Increasingly, Muhammadiyah became one of the organizations which had leaders in sub-district areas called branch leaders where the branch leadership became the second hand of the central leadership of Muhammadiyah in cities or districts. Community resources are very enthusiastic about establishing this leader in the area so that many become figures in the area so that they set up schools so that the people in the area have a good education. Muhammadiyah's role in the community is to make good cadres and spread the message of amar ma'ruf nahi mungkar.